2020
DOI: 10.1039/d0mt00034e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Fe metalloproteome of a ubiquitous marine heterotroph,Pseudoalteromonas(BB2-AT2): multiple bacterioferritin copies enable significant Fe storage

Abstract: Despite the extreme scarcity of Fe in seawater, the marine heterotroph Pseudoalteromonas has expansive Fe storage capacity and utilization strategies.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…In view of preponderant strains of Vibrio , Pseudoalteromonas , and Marinobacterium for 30 days, it was found that nutrients from Saharan dust in marine surface waters promoted the formation of Vibrio bloom, and dust-associated iron was a vital driving factor of Vibrio population dynamics ( Westrich et al, 2016 ). Besides, iron was extremely scarce in the marine, but Pseudoalteromonas with broad iron storage capacity can produce a large number of TonB iron complex transporters for obtaining iron ( Mazzotta et al, 2020 ). Marinobacterium species were commonly identified and were associated with metal corrosion processes, mainly in offshore oil structures ( Cluff et al, 2014 ; Brauer et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…In view of preponderant strains of Vibrio , Pseudoalteromonas , and Marinobacterium for 30 days, it was found that nutrients from Saharan dust in marine surface waters promoted the formation of Vibrio bloom, and dust-associated iron was a vital driving factor of Vibrio population dynamics ( Westrich et al, 2016 ). Besides, iron was extremely scarce in the marine, but Pseudoalteromonas with broad iron storage capacity can produce a large number of TonB iron complex transporters for obtaining iron ( Mazzotta et al, 2020 ). Marinobacterium species were commonly identified and were associated with metal corrosion processes, mainly in offshore oil structures ( Cluff et al, 2014 ; Brauer et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…The degree of competition between bacteria-phytoplankton is very sensitive to the modeled FL bacterial Fe demand and quotas, which are still poorly constrained at between 1e − 6 and more than 80e − 6 mol Fe/mol C by observations (Fourquez et al, 2015;Mazzotta et al, 2020;Tortell et al, 1996Tortell et al, , 1999). An elevated FL bacterial demand for Fe, either to meet their metabolic requirements or to build a large Fe internal storage through luxury uptake, enhances their competition with phytoplankton (Bowie et al, 2001;Ratnarajah et al, 2021) and the amount of Fe that is cycled through FL bacteria (Figure 12).…”
Section: Discussionmentioning
confidence: 99%
“…as described in details in Equation 19in Aumont et al (2015). The modeled FL bacterial Fe quota in PISCES varies between the minimum quota and a maximum Fe quota 𝐴𝐴 𝐴𝐴 𝐹𝐹 𝐹𝐹𝐹𝐹𝐹 max , which is set to 80e − 6 mol Fe/mol C (Mazzotta et al, 2020).…”
Section: Iron Quota In Fl Bacteriamentioning
confidence: 99%
See 2 more Smart Citations